Cuidados paliativos: relação dialógica entre enfermeira e crianças com câncer - França, Jael Rubia Figueiredo de Sá (2014)
INTRODUCTION: Palliative Care contemplates an approach of physical, social, psychological and spiritual treatment for patients without therapeutic possibilities and their families, in order to improve the quality of their lives. Its application is particularly important in the context of care focused on children with cancer, based on the Humanistic Nursing Theory. OBJECTIVES. To investigate how occurs the dialogical relation between the nurse and the child with cancer under Palliative Care, in light of the Nursing Humanistic Theory. METHODOLOGY: Field research, of qualitative nature, embodied in the Humanistic Nursing Theory, which the investigation scenario was the Support Center for Children with Cancer of Paraíba, located in João Pessoa PB. Participated in the study eleven children six male and five female. Data were collected from June to September 2013. For the production of empirical data it was used the technique of story-drawing. DATA ANALYSIS: Data were categorized and analyzed in light of the Humanistic Nursing Theory, with the following phases: preparation of cognizant nursing to come to the knowledge; the nurse knows intuitively the other; the nurse knows scientifically the other; the nurse complementarily synthetizes the known realities; succession of multiple for the paradoxical unit as internal process of the nurse. Data obtained were categorized in the following thematic categories: feeling of children with cancer: importance of pediatric palliative care; experiences of children during the oncological treatment: importance of pediatric palliative care and its subcategories: the search to minimize the repercussions before the oncological treatment and the faith in God before the situation experienced as power and hope for cure; Situations experienced by children with cancer under Palliative Care searching for diagnosis: importance of the dialogical relation; importance of playingin Pediatric Palliative Care: appreciation of joy, dialogue and company. RESULTS: The study showed the importance of Palliative Care, since the discovery of the disease, to minimize the suffering of children and their families. They highlight the family as force to propel them to face the disease from the faith in God. It was also pointed out that the Institutions of Health and others which form professionals should act jointly in meeting the children and their families; in response to the correct diagnosis and the beginning of the treatment and that playing, through the relation ME-YOU of the nurse with these children, bases on Palliative Care, allowed the development of an authentic therapeutic process. FINAL CONSIDERATIONS: The children surveyed shared a genuine care with the nurse through intersubjective relation between them, which resulted in meeting their necessities in the context of palliative care. This research open new horizons in the field of assistance, teaching and research in nursing, with emphasis in the valorization of dialogical relation between nurse and children with cancer without therapeutic possibilities of cure, grounded in palliative care. It is hoped that this can subsidize new investigation on the thematic, for they are still incipient studies that address interrelationship of Palliative Care with the Humanistic Theory with the children who experience this problem.